ANALISIS RELEVANSI METODE KLASIK TERHADAP TANTANGAN MODERNITAS, STUDY KASUS DI PONPES DAARUL MUWAHHIDIIN TANAH DATAR - doni rinaldo, doni rinaldo (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Islamic education in Indonesia has tended to change over time. In the pre-independence era, Islamic education consisted of Islamic boarding schools (pesantren) and halaqoh (religious study groups). During this period, the educational model remained classical and one-way. The kiyai, as the central teacher, taught his students through lectures in mosques, prayer rooms, or on the steps of the pesantren classrooms. However, with the advent of independence, the educational model of pesantren began to change to adapt to the times. This was especially true after the enactment of Law No. 4 of 1950 concerning Islamic Religious Education in Schools. Consequently, some Islamic boarding schools (pesantren) began reconstructing their learning models and curricula to align with government policies that allowed Islamic boarding schools to provide formal education, including junior high and senior high schools (SMP), MTs (Islamic junior high schools), and MA (Islamic junior high schools). This reconstruction also shifted the paradigm of Islamic boarding school education. The classical methods initially taught began to be updated with the addition of general subjects. However, there are certainly many challenges faced in the struggle for education in this Islamic boarding school. In this study, the researcher concluded that the Daarul Muwahhidiin Islamic boarding school provides an integrated education between classical and modern methods, which can be seen from the schools of thought that influence the development of the curriculum and the integrated curriculum structure in this Islamic boarding school. There are challenges in the form of difficulties in adapting for teachers teaching Islamic boarding school subjects when using learning media, while opportunities for Islamic boarding schools as character resilience amidst the decline in moral values ​​​​of society. This study used a descriptive qualitative method by conducting interviews, observations, and documentation to obtain research data.